Evaluation of Postoperative Pain and Discomfort in Patients Undergoing Surgical Exposure of Impacted Maxillary Canines - Gryte Zabielskaite; Mariam Varoneckaite; Dalia Smailiene (eJournal of Oral Maxillofacial Research, 2022)
Objectives: The purpose of the retrospective study was to evaluate pain and discomfort related to surgical exposure according to initial localization of impacted maxillary canines.